2010
DOI: 10.1002/adsc.201000344
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Water‐Soluble and Recyclable Organocatalyst for the Asymmetric 1,4‐Conjugate Addition of Nitroalkanes to α,β‐Unsaturated Aldehydes

Abstract: A novel strategy for the catalytic asymmetric conjugate addition of nitroalkanes to a,b-unsaturated aldehydes in aqueous media has been developed by using diarylprolinol silyl ether in combination with benzoic acid as a water-soluble organocatalyst providing the desired adducts in good to excellent enantioselectivities (up to 95% ee). This catalyst can be recycled at least five times with only a slight reduction in activity and selectivity. In addition, the synthetic procedure presented is simple, practical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…The enantioselectivity was determined by HPLC analysis (77% ee, Daicel CHIRALPAK AD-H, 5% isopropanol/hexane, 1.0 mL/min, 229 nm; t r (major enantiomer) = 18. Spectroscopic data of γ-nitroketones 4 are in agreement with published data [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. …”
Section: Typical Procedures For the Michael Addition Of Nitroalkanes Tsupporting
confidence: 81%
See 1 more Smart Citation
“…The enantioselectivity was determined by HPLC analysis (77% ee, Daicel CHIRALPAK AD-H, 5% isopropanol/hexane, 1.0 mL/min, 229 nm; t r (major enantiomer) = 18. Spectroscopic data of γ-nitroketones 4 are in agreement with published data [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. …”
Section: Typical Procedures For the Michael Addition Of Nitroalkanes Tsupporting
confidence: 81%
“…As pioneering works in organocatalytic asymmetric Michael addition of carbon nucleophiles to α,β-unsaturated carbonyl compounds, Yamaguchi's group reported that Michael addition of malonates to enones could be catalyzed by a proline alkali metal salt [6][7][8][9][10][11][12]. They later succeeded in the asymmetric Michael addition of nitroalkanes to enones using a proline rubidium salt-catalyst [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. We recently reported that an O-silylated L-serine lithium salt was an effective catalyst for asymmetric Michael addition of malonates to enones to give various 1,5-ketoesters in good yields with high enantioselectivity [33].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the same research group reported that diarylprolinol silyl ether 24 was shown to be highly effective when used in combination with benzoic acid as additive for the catalytic asymmetric conjugate addition of nitroalkanes to α,β-unsaturated aldehydes in aqueous media [66]. A major advantage of the catalytic system is the low donor nitroalkane loading of two equivalents.…”
Section: Methodsmentioning
confidence: 99%
“…Supported Jørgensen–Hayashi‐type catalysts 2 – 5 that contain polymeric,16 dendritic,17 perfluoroalkyl,18 ionic,19 or paramagnetic groups20 have been prepared so far (Scheme ). However, in most cases they became much less active after 1–3 regenerations no matter which modifying group or reagents were used,16a,b,d,e, 18, 19f,g, 20 whereas enantioselectivity remained almost at the same level 16a,b,e. 18, 19f,g, 20 The significant deactivation cannot be explained by the catalyst “leaching” during the extraction of products, because its mass loss after the recovery was usually no more than 10 wt % per cycle 17.…”
Section: Introductionmentioning
confidence: 99%